Pengembangan Kawasan Strategis Minapolitan Studi Kasus Kecamatan Belopa Utara Kabupaten Luwu - suryandi yusuf; Rahmawati Rahman; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
The fishery sector is one of the economic sectors that has contributed significantly to the economy of Luwu Regency, production activities to the distribution of fishery products in the Minapolitan area require a spatial structure plan for the coastal area to be developed by accommodating the concept of the Minapolitan spatial structure which has become a sectoral guideline in Luwu Regency. Based on this, it is necessary to direct the development of the Minapolitan area through the identification of the factors that influence the development of the minapolitan area of ​​North Belopa District. This type of research is descriptive with qualitative and quantitative approaches, with qualitative descriptive analysis techniques, quantitative correlation, physical conditions and availability of infrastructure facilities, fisheries-based sector, as well as directions for the development of the minapolitan area. Based on the results of the analysis of the availability of facilities in the Minapolitan area, 73.7% (good category), with potential for fishery production, namely Seaweed, Garacillaria, Milkfish, and Windu Shrimp. The zoning directions for the Minapolitan area in North Belopa Sub-district are divided into four zones, namely the Mina City Core Zone which is directed at Seppong Village and Pammanu Village, the Mina City Production Center Zone is directed at Paconne Village and Sabe Village, the Development Zone is directed at Lamunre Tengah Village, and Zone The linkage is directed to areas that are the target of marketing products in the North Belopa District, namely Lebani Village, Lauwa Village.